The construct validity and reliability of the lesson plan assessment instrument in primary schools - Lian Gafar Otaya; Badrun Kartowagiran; Heri Retnawati (Jurnal Prima Edukasia, 2020)
This study aims to prove the construct validity of the lesson plan assessment instrument in primary schools. In addition, the purpose of this study is to estimate the reliability of lesson plan instruments in primary schools. This research uses a descriptive quantitative approach that is carried out on professional teacher education students at Universitas Negeri Gorontalo, Universitas Negeri Yogyakarta and Universitas Islam Negeri Makassar. The subjects of this study were 516 randomly selected students. Data collection is done through documentation of the results of assessments from the field supervisor of each student. The data analysis technique used is confirmatory factor analysis and composites score reliability. The results showed that the lesson plan assessment instrument was measured by 25 items spread over 4 indicators. All items in the lesson plan assessment instrument indicators are construct valid after being tested through confirmatory factor analysis. In addition, the lesson plan assessment instrument in this study was reliable and had a fairly high construct reliability coefficient of 0.92.